Pathfinders of the West; being the thrilling story of the adventures of the men who discovered the great Northwest, Radisson, La Vérendrye, Lewis and Clark - Laut, Agnes C. (Agnes Christina), 1871-1936. (New York, The Macmillan company; London, Macmillan & co., ltd., 1922)
pt. 1. Pierre Esprit Radisson.--pt. 2. The search for the western sea, being an account of the discovery of the Rocky mountains, the Missouri uplands, and the valley of the Saskatchewan.--pt. 3. Search for the Northwest passage leads Samuel Hearne to the Arctic circle and Athabasca region.--pt. 4. First across the Rockies--How Mackenzie crossed the northern Rockies and Lewis and Clark were first to cross from Missouri to Columbia. Mode of access: Internet.